Ein Gartenfest vor hundert Jahren. (Danzig : [s.n.], 1918)
Druk inf. o festynie wraz z programem (czerwiec 1918).
Keywords: Wojna światowa (1914-1918) -- Polska -- Gdańsk -- druki ulotne; Gdańsk (Polska) -- 1900-1945 -- druki ulotne